(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The effects of addition of Bagasse ash and Sisal Fibers in soil on MDD and OMC relationship different percentages of bagasse ash is added and optimized. Then this optimized bagasse ash soil is the mixed with the different lengths and different percentages of Sisal Fibers. It is interpreted that there is increase in OMC and decrease in MDD with addition of Bagasse Ash. But the values of CBR and UCS are increased with 4% of BA and Sisal Fiber length 4cm at 1.5%. There is increase in the percentage of UCS, when sample were prepared with 2%, 4% by 3.02%, 4.70% and decrease in percentage of UCS,. The experiments in combined sample of BA and Sisal Fiber (2cm, 4cm, 6cm)shows that the maximum value of UCS are obtained at 4cm length with 1.5% by weight, which is found to be 3.73 kg/cm2. The percentage increase as compared to the raw soil is 25.16%. The soaked CBR value of the raw soil with 4% BA is 2.59%. The soaked CBR value of combined soil sample with 4% BA, 1.5% of Sisal Fiber of 4cm length is found to be 3.09%, the increase in CBR value as compared to raw soil is 70.16%.